Epiplakin Deficiency Aggravates Murine Caerulein-Induced Acute Pancreatitis and Favors the Formation of Acinar Keratin Granules - Wögenstein, Karl L. (Public Library of Science, 2014)
Epiplakin, a member of the plakin protein family, is exclusively expressed in epithelial tissues and was shown to bind to keratins. Epiplakin-deficient (EPPK(−/−)) mice showed no obvious spontaneous phenotype, however, EPPK(−/−) keratinocytes displayed faster keratin network breakdown in response to stress. The role of epiplakin in pancreas, a tissue with abundant keratin expression, was not yet known. We analyzed epiplakin’s expression in healthy and inflamed pancreatic tissue and compared wild-type and EPPK(−/−) mice during caerulein-induced acute pancreatitis. We found that epiplakin was expressed primarily in ductal cells of the pancreas and colocalized with apicolateral keratin bundles in murine pancreatic acinar cells. Epiplakin’s diffuse subcellular localization in keratin filament-free acini of K8-deficient mice indicated that its filament-associated localization in acinar cells completely depends on its binding partner keratin. During acute pancreatitis, epiplakin was upregulated in acinar cells and its redistribution closely paralleled keratin reorganization. EPPK(−/−) mice suffered from aggravated pancreatitis but showed no obvious regeneration phenotype. At the most severe stage of the disease, EPPK(−/−) acinar cells displayed more keratin aggregates than those of wild-type mice. Our data propose epiplakin to be a protective protein during acute pancreatitis, and that its loss causes impaired disease-associated keratin reorganization.